Efektivitas Media Cerita Bergambar Interaktif dalam Meningkatkan Literasi Membaca Permulaan - Rina Kartika; Fajar Nugroho; Aulia Nurhasanah (Gema Cendekia Institute, 2026)
ABSTRACT This study aims to determine the effectiveness of interactive picture story media in improving the early reading literacy of second-grade elementary school students. Early reading literacy in this study includes the ability to recognize letters, read syllables, read simple words, read short sentences, and understand the content of simple reading. The study used a quantitative approach with a quasi-experimental design in the form of a One Group Pretest-Posttest Design. The subjects were second-grade elementary school students selected using a total sampling technique. Data were collected through early reading tests (pretest and posttest), student activity observation sheets, and student response questionnaires regarding the use of the media. Test data were analyzed using normality tests, paired sample t-tests, and N-Gain calculations to determine the level of improvement in students' reading abilities. The results showed that the use of interactive picture story media significantly improved students' early reading literacy. This improvement was evident in higher posttest scores compared to pretest scores, particularly in aspects of fluency in reading syllables and simple words, ability to read short sentences, and comprehension of reading content. Furthermore, observations showed increased student activity and engagement during the learning process. Student responses also showed positive results, with most students finding the media engaging, easy to use, and helpful in their reading comprehension. Thus, interactive picture stories can be an effective, innovative alternative for improving early reading literacy in elementary school students.